Упростите выражение (x^-1 - 2y^-3)^2 + 4x^-1y^-3 и 6x^-2y^-1 + (3y^-1 - x^-2)

0 голосов
47 просмотров

Упростите выражение
(x^-1 - 2y^-3)^2 + 4x^-1y^-3
и 6x^-2y^-1 + (3y^-1 - x^-2)


Математика (12 баллов) | 47 просмотров
Дан 1 ответ
0 голосов

1. a) 1 + (0.5x-3) - (1.5x-4) = 1 + 0.5x - 3 - 1.5x + 4 = 2 - x
   б) 1 - 4 (1/2y + 1) + 5 (0.2 - y) = 1 - 2y - 4 + 1 - 5y = - 7y - 2 
2. Решение: 
Пусть AB = x, тогда CB = 2x, AC = 2x-4, т.к Периметр = 21 => 
x+2x+2x-4=21
5x = 21+4
5x=25
x=5
=> AB = 5, CB = 2 * 5 = 10, AC = 2*5-4 = 6
Ответ: AB = 5, CB = 10, AC = 6
3. Решите уравнение:
a) 2(2.5x-1)= - (1.8-4x)
    5x-2=-1.8+4x
    5x-4x=2-1.8
    x = 0.2
б) 10x-(2x-4) = 4(3x-2)
    10x-2x+4=12x-8
    8x-12x = -8 -4
    -4x = -12
    x = 3
в) 16(0.25x-1) = 5(0.8x-3.2)
    4x-16 = 4x-16
    0 = 0 
    Нет Решения
4. ---- если так скажи спасибо

(56 баллов)